Propuesta de identidad para la marca de pañuelos sostenibles “Adelina” - Tuesta Vascones, Brunela (2021)
In the following project we support and describe a proposal for a visual identity creation process for Adelina, a sustainable brand of timeless scarves. As part of this proposal, the new identity of the brand was defined, from its personality to the visual proposal. Within its visual proposal, some elements such as typography, color palette and photography were determined so that, with its constant use, it achieves coherent communication in all its channels and, in turn, can easily position itself in the market. All the above has been compiled in a document known as the brand manual in which all the guidelines and correct uses are included. Also, an animation for the logo was developed.